1997
DOI: 10.1088/0022-3727/30/19/010
|View full text |Cite
|
Sign up to set email alerts
|

Ionization phenomenon in high-density gaseous and liquid argon in corona discharge experiments

Abstract: Experimental investigations of corona discharge in Ar for a wide region of fluid density from a rare gas up to a liquid have been carried out. Corona current has been observed for a point cathode voltage above the threshold value . Values of have been measured for a wide range of fluid density N and for different cathode radii . The obtained dependences of on N and have been analysed using the Townsend - Meek breakdown criterion. For low-density gas the calculations of have been carried out by using univer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 23 publications
(60 reference statements)
1
16
0
Order By: Relevance
“…Electron scattering, attachment, and energy loss near the critical point are apparently anomalous because negative charges show the lowest mobility near the critical point [25], and breakdown (or corona onset) voltages show a transition near the critical point [11][12][13][14][15]. Bonifaci et al reported that the transition might be explained by a reduced electron-impact excitation cross section [12]. More electron-impact chemical activation could also be achieved with lower energy loss of the electron (higher electron energy).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Electron scattering, attachment, and energy loss near the critical point are apparently anomalous because negative charges show the lowest mobility near the critical point [25], and breakdown (or corona onset) voltages show a transition near the critical point [11][12][13][14][15]. Bonifaci et al reported that the transition might be explained by a reduced electron-impact excitation cross section [12]. More electron-impact chemical activation could also be achieved with lower energy loss of the electron (higher electron energy).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, if an unstable/dynamic microscopic structure were used efficiently, then the so-called 'clustering' could be used for processing, such as that observed in anomalous reaction rates near the critical point [10]. Thereby, we might be able to achieve plasma processing that is novel and unique -differing from plasma processing in either gas or liquid; perhaps such a novel method could be supported, in part, by the transition in breakdown (or corona onset) voltages near the critical point [11][12][13][14][15] and density fluctuation near the critical point with discharge plasma [16]. High-speed processing and unique processing might be the two strongest incentives for studying this novel processing environment.…”
Section: Introductionmentioning
confidence: 99%
“…High ionisation coefficient [3,4] and high electron temperature in Ar cause that the discharge in this gas starts at lower voltages than for other gases tested. The bright point becomes a new source of ions of polarity opposite to that of the discharge electrode.…”
Section: Resultsmentioning
confidence: 99%
“…Discharges in liquids are intensively studied because of their use in many application fields, like electrical power systems, [1,2] plasma electrolytic oxidation, [3,4] electrical discharge machining (EDM), [5,6] nanomaterials synthesis, [7,8] and more recently bio-medical applications. [9,10] Interaction of discharges with electrodes is a complex topic, especially in microgap conditions where diagnostics are difficult to perform.…”
Section: Introductionmentioning
confidence: 99%